Review of mastectomy in the department of gynecology at the Treichville teaching hospital, Abidjan-Cote d’Ivoire - N’guessan, Yao Ignace; Lamine, Dia Jean-Marc; Moctar, Toure; Corneille, Saki Téa; Gilbert, Tela Simo; Adunfé, Oyelade Mouhideen; Gérard, Okon; Privat, Guie Yéret; Simplice, Anongba Danho (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Mastectomy plays a key role in the management of breast cancer in our regions of sub-Saharan Africa. Because the advanced forms represent the essential stages of the diagnosis and some therapeutic means remain unavailable. Objective of this study was to report the experience of the practice of mastectomy in the treatment of breast cancer in our service. Methods: This is a retrospective and prospective, descriptive study conducted from January 1, 2013 to May 31, 2017 (age 05) at the University Hospital of Treichville involving 56 breast cancer patients who had undergone a mastectomy. Results: The frequency of the mastectomy was 28.5% and the average age of our patients was 48 years old. The majority of patients had an average socio-economic level (66%). 85.6% of our cancers discovered at advanced stages (T3 and T4). Adenocarcinoma accounted for 96% and infiltrating ductal carcinoma 82% of adenocarcinoma. Patey mastectomy associated with axillary dissection was performed in 96.4% and simple mastectomy in 3.5%. The results of axillary dissection reported lymph node invasion in 38 patients; With an average number of lymph nodes taken from 6.1 and an average number of ganglia affected is 3. Neoadjuvant chemotherapy was administered in 96.4% and adjuvant chemotherapy in 91%. Radiotherapy was performed in 34%. Complications were dominated by lymphoceles in 34% of cases. The 5-year survival of patients operating in the service is 37.8%. Conclusions: Mastectomy is at the forefront of breast cancer surgery in our service. She is supervised by chemotherapy. Radiotherapy remains inaccessible for most patients. Early detection would lead to conservative treatment and a reduction in the postoperative complication rate.